2020
DOI: 10.1155/2020/3236841
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Headway-Based Control Method to Improve Public Transit Reliability considering Control Points Layout

Abstract: The headway-based control method is usually used to regulate the bus headways and improve reliability of public transit. In general, the holding control strategy is applied at the control point, because enough space for dwell longer at the control point is required, while the stop-skipping control strategy can be used at any bus stop. However, in the headway-based control method, too much stop-skipping will bring longer waiting time and make the passengers impatient. The number and distribution of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/2399-9802.htm two classes: scheduled-based method (Steiner and Irnich, 2018;Kumar et al, 2019;Chen and Sun, 2019) and headwaybased method (Zhang et al, 2020;Gkiotsalitis and Cats, 2018;Zhang and Lo, 2018). In the former group, the control is implemented according to the bus schedules, aiming at improving bus schedule adherence at each station, which is appropriate for low frequency transit lines, whereas headwaybased strategy is designed to keep headway close to the ideal along the route, and this method can be applied to high frequency transit lines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/2399-9802.htm two classes: scheduled-based method (Steiner and Irnich, 2018;Kumar et al, 2019;Chen and Sun, 2019) and headwaybased method (Zhang et al, 2020;Gkiotsalitis and Cats, 2018;Zhang and Lo, 2018). In the former group, the control is implemented according to the bus schedules, aiming at improving bus schedule adherence at each station, which is appropriate for low frequency transit lines, whereas headwaybased strategy is designed to keep headway close to the ideal along the route, and this method can be applied to high frequency transit lines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Song [12] used GPS data to obtain the stopping time data of the bus, and used the average stopping time and travel time stability coefficient as indicators to classify the control points into two categories that need to be controlled and can be controlled for a step-by-step solution, with a simple process of local derivation, but the selected solution may not be the overall optimal result. Zhang et al [13] evaluated the performance of control points with different numbers and different distributions through a set of examples, and the results showed that the distribution of control points outweighed the effect produced by their number.…”
Section: Introductionmentioning
confidence: 99%
“…One of these options is to increase the number of PT trip by increasing the speed of communication and reducing the time delays when crossing intersections. This can be achieved through the creation of lanes for PT and the introduction of the crossing intersections priority for PT [5]- [7].…”
Section: Introductionmentioning
confidence: 99%